Flash mobile : developing Android and iOS applications - David, Matthew, 1971- (Focal Press, 2011)
Build rich media applications for the iOS and Android platforms with this primer to Flash mobile development. You get all of the essentials-from setting up your development environment to publishing your apps to the Google Market Place/Apple iTunes App Store. Develop elementary applications without coding; then realize the power of ActionScript 3 to add rich complexity to your applications. Step-by-step instruction is combined with practical tutorial lessons to deliver a working understanding of the development stages.